Impact of EGFR-TKI Treatment on the Tumor Immune Microenvironment in EGFR Mutation–Positive Non–Small Cell Lung Cancer - Isomoto, Kohsuke; Haratani, Koji; Hayashi, Hidetoshi; Shimizu, Shigeki; Tomida, Shuta; Niwa, Takashi; Yokoyama, Toshihide; Fukuda, Yasushi; Chiba, Yasutaka; Kato, Ryoji; Tanizaki, Junko; Tanaka, Kaoru; et al. (Clinical cancer research, 2020)
The impact of EGFR tyrosine kinase inhibitors (TKI) on the tumor immune microenvironment (TME) in non-small cell lung cancer (NSCLC) is unclear. We retrospectively identified 138 patients with -mutated NSCLC who underwent rebiopsy after progression during EGFR-TKI treatment. PD-L1 and CD73 expression in tumor cells and tumor-infiltrating lymphocyte (TIL) density at baseline and after progression were determined by IHC. Tumor mutation burden (TMB) was determined by next-generation sequencing. The proportion of patients with a PD-L1 expression level of ≥50% (high) increased from 14% before to 28% after EGFR-TKI ( = 0.0010). Whereas CD8 and FOXP3 TIL densities were significantly lower after EGFR-TKI treatment than before, CD8 TIL density was maintained in tumors with a high PD-L1 expression level. Expression of CD73 in tumor cells after EGFR-TKI treatment was higher than that before in patients with a high PD-L1 expression level. TMB tended to be higher after EGFR-TKI treatment than before (3.3→4.1 mutations/Mbp, = 0.0508). Median progression-free survival for subsequent treatment with antibodies to PD-1 was longer for patients with a high than for those with a low PD-L1 expression after EGFR-TKI (7.1 vs. 1.7 months, = 0.0033), and two of five patients whose PD-L1 expression level changed from low to high after EGFR-TKI treatment achieved a PFS of >6 months. EGFR-TKI treatment was associated with changes in the TME of -mutated NSCLC, and such changes may provide clues for optimization of subsequent PD-1 inhibitor treatment.